Laws and Ordinances for the Government of the Municipal Corporation of the City of Williamsport 141 (1891) - (:unkn) unknown (My University, 1891)
An ordinance prescribing the rules and regulations for the government and protection of Brandon Park, § 21: Prohibited carry of fire-arms, shooting in the park, discharging fire-works, throwing stones, or throwing missiles within the limits of Brandon Park
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE